Assessing the effects of price regulation and freedom of choice on quality: Evidence from the physiotherapy market - Piia Pekola; Ismo Linnosmaa; Hennamari Mikkola (Health Economics Review, 2017)
In health care, many aspects of the delivery of services are subject to regulation. Often the purpose of the regulated health care system is to encourage providers to keep costs down without skimping on quality. The purpose of this paper is to analyse the effect of price regulation and free choice on quality in physiotherapy organised by the Social Insurance Institution of Finland for the disabled individuals. We use the difference-in-differences method in our effort to isolate the effect of the regulation and for this task we have defined the regulated and non-regulated firms and their quality before and after the regulation. The variables needed in the econometric modelling were collected from several registers as well as by carrying out questionnaires on the firms. We show that price regulation decreased quality in physiotherapy statistically significantly and the mechanism was unable to incentivise firms to invest in quality. Most likely, our results are caused by cost reduction associated with price regulation. It seems that cost reduction was carried out through quality reductions in physiotherapy instead of increasing productivity. The result is sensible because comparable quality information is not published to support patient choice in this sector.
Keywords: I11; I18; L15; L51; 330; Competitive bidding; Financial incentives; Physiotherapy; Quality; Regulation; Service voucher